Separation of the Polypeptides of Chlamydia and Its Cell Walls by Polyacrylamide Gel Electrophoresis - Tamura, Akira (1974)
The polypeptide composition of Chlamydia was examined by acrylamide gel electrophoresis. When the polypeptide patterns of purified infectious elementary bodies (EB) of C. psittaci meningopneumonitis strain, 6BC strain, and C. trachomatis T'ang strain were compared, no significant differences were observed. The polypeptide patterns of whole EB and reticulate bodies (RB) appeared to overlap, but differences were found. In EB cell walls, nine main and several minor bands of polypeptides were observed in gels containing sodium lauryl sulfate, and the eighth main band from the top of the gel stained positive with periodic acid-Schiff reagent. On the other hand, the polypeptides in bands 3, 6, and 8 in EB cell walls were missing or minor in RB cell walls, and the ninth band was clearly stained by PAS. Band 8 was also stained slightly. Purified subunits, which occur as a lattice structure on the inside layer of EB cell walls but are largely missing in RB cell walls, contained bands 4, 6, and 8, and band 8 was PAS positive. These results indicate that significant polypeptide synthesis or reorganization in the cell walls occurs during the growth cycle.